Strength Characteristics of Reinforced Sandy Soil - S. N. Bannikov; Mahamed Al Fayez (Наука и техника)
Laboratory tests on determination of reinforced sandy soil strength characteristics (angle of internal friction, specific cohesive force) have been carried out with the help of a specially designed instrument and proposed methodology. Analysis of the obtained results has revealed that cohesive forces are brought about in reinforced sandy soil and an angle of internal soil friction becomes larger in comparison with non-reinforced soil.